Quick Response Code Indonesian Standard (QRIS), Penjualan dan Kepuasan Pelanggan: - Ayu Indriani; E. Mulya Syamsul; Ayu Gumilang Lestari (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Quick Response Code Indonesian Standard (QRIS) is the most efficient instant payment method which is a collaboration product between Bank Indonesia and the Indonesian Payment System Association (ASPI). QRIS as the latest server-based non-cash payment method that is integrated with digital wallets has been used in retails or minimarkets such as Alfamart. The use of server-based electronic money with digital wallets is very popular today. The purpose of this study is to reveal whether the use of QRIS can have an impact on Alfamart Talaga Wetan's sales profit and how Alfamart's customer satisfaction after using QRIS. The research method used is a naturalistic qualitative method to reveal the actual state of social phenomena that are tentative (temporary). Data collection techniques were carried out through observation, interviews and documentation methods. The result of this study is that QRIS has an impact on Alfamart Talaga Wetan's sales profit as seen from the BAP reports in May, June and July 2022 which had a significant impact. The use of QRIS also has an impact on Alfamart's customer satisfaction, seen from the answers of 8 interviewees who all agreed that they were satisfied because QRIS can help speed transactions and minimize queues.